PERBANDINGAN PENGGUNAAN ASPAL PERTAMINA PEN 60/70 DAN ASPAL BUTON BUTIR TYPE 5/20 DALAM PEKERJAAN JALAN - Yanshon Happy; Yosevina . (Huma Tabalien Jurnal (HTJ) Teknik Sipil, 2021)
Asphalt is a binding material in flexible pavement construction which is very influential. To get good quality asphalt, it can be done by modifying the asphalt mixture with an additional material. With this planning, this study specifically aims to determine the properties of asphalt to the asphalt mixture Pertamina Penetration 60/70 with Buton Buton Asphalt Type 5/20, to test the mixture with Marshall tools and to find the optimum bitumen content. The research method starts from material testing using the SNI test method by testing the physical properties of the aggregate with a combination of mixing Pertamina Asphalt and Buton Asphalt as a binding material with the Marshall Test test method. The research was conducted at the Jalan Raya Laboratory owned by PT. Sampaga Raya on Jl. H.M. Arsyad Km. 24 Bagendang, Sampit - Central Kalimantan. Based on the results of research on the examination of the physical properties of aggregates in the form of inspection of grading, specific gravity, sand equivalent, and wear (abrasion), they have met the specifications set for the Laston Lapis Aus (AC-WC) mixed material with a mixed combination using Asphalt Pertamina Penetration 60 / 70 and the combination of Asphalt Buton Butir Type 5/20 mixture obtained the physical properties and Marshall parameters in the form of stability, flow, and Marshall quotient values which are quite good in meeting the specification standards set for the pavement layer. Keywords: Aggregate Gradation, Specific Gravity, Sand Equivalent, Wear (abrasion), Asphalt Pertamina Pen 60/70, Asphalt Buton Type 5/20, Marshall Test.